ANALYSIS OF THE IMPACT OF THE IMPLEMENTATION OF MICE (Meeting, Incentive, Convention and Exhibition) ON INCREASING SALES AND MARKET DEVELOPMENT FOR MSME PLAYERS IN TEBING TINGGI CITY IN THE ERA INDUSTRIAL REVOLUTION 4.0 - Dwi Arseto, Dedy; Hutagalung, Hermanto (CV. Radja Publika, 2022)
This study aims to determine the impact of MICE (Meeting, Incentive, Convention and Exhibition) on increasing sales and market development for MSME players in Tebing Tinggi City in the Industrial Revolution Era 4.0. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to MSME actors in the city of Tebing Tinggi who participated in MICE as many as 80 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, multicolonearity test, heteroscedasticity test, simple linear regression analysis, hypothesis testing, namely the T test. The results of SPSS in this study, namely MICE (Meeting, Incentive, Convention and Exhibition) have an effect on increasing sales and market development for players MSMEs in Tebing Tinggi City in the Industrial Revolution 4.0 Era.